New challenges to privacy due to emerging technologies and different privacy perceptions of younger generations: The EU PRACTIS project. - Ahituv Niv; Bach Nicolas; Birnhack Michael; Soffer Tal; Luoto Liisa (My University, 2022)
PRACTIS (Privacy Appraising Challenges to Technologies and Ethics) is a research project initiated by the EU. It was carried out over three and one half years by research institutes of six countries: Israel (project coordinator), Poland, Germany, Finland, Belgium, and Austria. PRACTIS was concluded in April 2013 with the submission of a list of recommendations to the EU.
PRACTIS focused on three major research tracks: Technological forecast, ethics and legal aspects of privacy, and the changing perception of privacy among younger generations (Internet "natives").
This paper consists of two parts. The first part describes one of the most interesting studies which were carried out within PRACTIS – the high-school children survey about their perception of privacy. The second part outlines some policy recommendation mostly for governments and regulators.
The major conclusion of the high-school survey indicates that there is, indeed, a different perception of privacy among teenagers. For them, the individual sphere in which they wish to protect their privacy is not limited only to their immediate physical environment (home, diary, body), but it is expanded also to their virtual environment such as social networks sites (SNS). They are also willing to trade benefits provided by the digital environment for privacy.
The major recommendation conveyed to the EU is that there is no one "deus ex machine" solution to the threats privacy faces due to emerging technologies such as ICT, Genetics, Nanotechnology, Cognitive and Brain Sciences, and the like. There should be a comprehensive strategy and policy and a basket of solutions adhering to technology, law and regulations, organizational issues, education, and social issues. A detailed list of recommendations is exhibited in the article.
Informing Science & IT Education Conference (InSITE)